A socio-cognitive analysis of evaluation and idea generation activities during co-creative design sessions supported by spatial augmented reality. Issue 1 (2nd January 2021) - Masclet, C.; Boujut, J.-F.; Poulin, M.; Baldaccino, Laetitia
ABSTRACT: Co-creation with end-users is gaining an increasing interest in the design industry today. This study investigates the mechanisms by which spatial augmented reality (SAR) technology can affect socio-cognitive processes in groups involved in co-creative design sessions. More precisely, when used in real co-creative design sessions, does a SAR system facilitate the collective creative process, compared to sessions occurring in standard settings? A protocol analysis has been conducted to investigate three different design sessions involving experienced designers and end-users on a product design task: a design session supported by conventional design representations (usual design practices), a design session supported by non-spatial augmented reality (AR), and a session supported by SAR technology. While results do not clearly show that SAR or AR technologies increase end-user's commitmen t, they illustrate the ability for these technologies to allow browsing through more ideas during a co-creative design session. Furthermore, it tends to reduce time spent on ideas, compared to a traditional session. We also noted that the introduction of this technology does not modify the profiles of the sessions in terms of cognitive activities. This tends to demonstrate that the technology itself does not impair the design activity.